Extreme events os precipation and occurrences of flooding, runoff and inundation in the metropolitan region of Curitiba, Brazil - Caldana, Nathan Felipe da Silva; Rodrigues, Leonardo; Ferreira, Luis Gustavo Batista; de Aguiar e Silva, Marcelo Augusto (Geografia em Questão, 2021)
Extreme precipitation events cause severe damage in both urban and rural areas. The objective of this work was to analyze rainfall variability, understand the dynamics of extreme precipitation events and to find out the occurrence of floods, runoff and inundation in the Metropolitan Region of Curitiba (MRC). Data from 39 rainfall stations distributed in the MRC area were used, as well as data by municipality of occurrence of flooding, runoff or inundation, from 1976 to 2018. Extreme precipitation events were identified in all months, most frequently in the summer. Totaling 48 decrees of emergency or public calamity and 397,516 people affected by one of the three socioenvironmental disasters.